Melt Phase Polymerization of Racemic Lactide to High‐Performance Poly(Lactic Acid). Issue 4 (26th February 2014) - Paetz, Caspar; Hagen, Rainer; Klemm, Elias; Sauer, Jörg
Abstract A process for the production of poly(lactic acid) with a melting point of > 150 °C from racemic lactide was developed. Only process steps that are usable in an industrial process were included to ensure an easy transfer to a commercial scale. A stereoselective catalyst system for lactide melt phase polymerization comprising of an Al‐salen initiator, a hydroxyl cocatalyst and an acidic quenching additive was developed. Monomer recovery aspects, temperature variation and different catalyst concentrations were evaluated to allow for a high yield process which can be transferred to a technical scale.